Kepentingan Nasional Indonesia dalam Meratifikasi Perjanjian Biodiversity Beyond National Jurisdiction (BBNJ) - Joel P. N. Talaperu; Triesanto R. Simanjuntak; Novriest U. W. Nau (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2024)
The Biodiversity Beyond National Jurisdiction Agreement (BBNJ Agreement) is a new international legal instrument formed to increase the use and conservation of biodiversity outside national jurisdiction. The BBNJ Agreement was formed because there was a vacuum in the 1982 UNCLOS regulations related to activities and protection of biodiversity outside national jurisdiction (Areas Beyond National Jurisdiction/ABNJ), to debates between developed and developing countries regarding access and technological capacity used to utilize biodiversity outside the jurisdiction. nationally by all countries. Indonesia is one of the countries that is actively taking part in the BBNJ Agreement, from the formation process to ratification in 2023. This research was carried out through a literature study method, using the concept of national interests and rationality theory, and observing the absence of ABNJ regulations in UNCLOS 1982, regulation of biodiversity in Indonesia which then resulted in the argument that in this research stated that Indonesia is a rational actor, through which the BBNJ Agreement can strengthen Indonesia's position as a maritime country so that it can be part of the protection and utilization of biodiversity outside national jurisdiction (Indonesia's Global Maritime Axis). Moreover, this multilateral cooperation framework allows Indonesia to benefit from fair profit sharing, as well as the transfer of technological capacity for biodiversity exploration outside national jurisdiction.